The Arctic Cisco (Coregonus autumnalis) Subsistence and Commercial Fisheries, Colville River, Alaska: A Conceptual Model - Fechhelm, Robert G.; Streever, Bill; Gallaway, Benny J. (ARCTIC, 2009)
The arctic cisco (Coregonus autumnalis), known regionally by its Inupiat name qaaqtaq, is the principal target of fall subsistence and commercial fisheries that operate in the Colville River along the Alaskan Beaufort Sea. Our conceptual model of the fisheries is based on more than two decades of continuous scientific study conducted in conjunction with oil industry growth on the North Slope. It expands upon an existing body of published literature to discuss additional factors that affect fishery yields. Long-term data indicate that arctic cisco spawn in Canada’s Mackenzie River system. Young-of-the-year are transported westward into Alaska by wind-driven coastal currents. Arctic cisco successfully recruit to Alaska’s Colville River when summer winds blow from the east with an average speed greater than 5 km/h. The successful recruitment of these young arctic cisco to central Alaska is a prerequisite for the eventual entry of harvestable five- to eight-year-old fish into the region’s subsistence and commercial fisheries. Recruitment into the fisheries also requires that fish survive in central Alaska for the five to six years it takes for them to grow to a harvestable size. Once these fish are recruited into the fisheries, annual harvests are strongly dependent on salinity conditions within the fishing grounds. Although fishing mortality occurs, the loss of older fish from the region is attributed largely to the emigration of sexually mature fish back to Canada. Le cisco arctique (Coregonus autumnalis), connu régionalement sous le nom de qaaqtaq en inupiat, est la principale cible des pêcheries commerciales et de la subsistance d’automne de Colville River, le long de la partie alaskienne de la mer de Beaufort. Notre modèle conceptuel des pêcheries repose sur une étude scientifique réalisée sans arrêt pendant plus de deux décennies à la lumière de l’essor connu par l’industrie du pétrole sur la côte Nord. Il s’appuie également sur de la documentation publiée et englobe d’autres facteurs qui ont une incidence ...